Modelling Feedback Control Loops for Self-Adaptive Systems - Nzekwa, Russel Aime; Rouvoy, Romain; Seinturier, Lionel (Electronic Communications of the EASST, 2010)
Feedback Control Loops (FCLs) are the heart of any self-adaptive sys- tem. Existing engineering approaches for building self-adaptive systems mask FCL by providing abstraction layers that hide the application complexity. In this paper, we investigate a model-driven approach for the engineering of FCLs whose archi- tecture is based on the Service Component Architecture (SCA) model. Our proposal consists in exploiting the data streaming model, to specify the characteristics of the control policies, and to generate FCLs of self-adaptive systems deployed in large- scale environment. We argue that the use of a data-oriented model for designing self-adaptive systems significantly increases FCL visibility.